Pinitol Improves Lipopolysaccharide-Induced Cellular Damage in Human Dermal Microvascular Endothelial Cells - Min Young Go; Jinsick Kim; Chae Young Jeon; Mujun Kim; Dong Wook Shin (Molecules)
3-O-Methyl-D-chiro-inositol (pinitol) has been reported to possess insulin-like effects and is known as one of the anti-diabetic agents for improving muscle and liver function. However, the beneficial effects of pinitol on human dermal microvascular endothelial cells (HDMECs) are not well understood. In this study, we investigated whether pinitol could protect HDMECs from damage induced by lipopolysaccharides (LPSs), which cause various cell defects. We observed that pinitol enhanced wound healing for LPS-damaged HDMECs. We found that pinitol significantly downregulated the LPS-induced upregulation of reactive oxygen species (ROS). Pinitol also significantly restored the mitochondrial membrane potential in these cells. Immunofluorescence analysis revealed that pinitol notably reduced the nuclear localization of NF-κB in LPS-damaged HDMECs. Furthermore, we demonstrated that pinitol decreased the phosphorylation levels of the MAPK family in LPS-damaged HDMECs. Interestingly, we observed that pinitol improved tube formation in LPS-damaged HDMECs. Taken together, we suggest that pinitol exerts several beneficial effects on LPS-damaged HDMECs and may be a promising therapeutic agent for improving vascular-related skin diseases.